A lingua franca for concurrent logic programming - Taylor, H. (IEEE transactions on software engineering, 1992)
Two of the more important concurrent logic programming languages with nonflat guards are GHC and Parlog. They balance the requirements of having clean semantics and providing good control facilities rather differently, and their respective merits are compared and contrasted. Since concurrent logic programming would benefit from both, but neither language is able to express all the programs expressible in the other language, a lingua franca of these languages is defined and justified. A method is given for translating GHC and Parlog to and from it. The method preserves the arities and execution conditions of each clause. It enables a lingua franca implementation to support both languages transparently, and to provide a simple concurrent logic programming language suitable for programming in its own right.< >